Evaluation of Open Defecation Free (ODF) Policy in Pangandaran Regency in 2024 - Anisah Anisah; Budi Aji; Arih Diyaning Intiasari (Green Publisher Indonesia, 2025)
Proper sanitation is a crucial factor in creating a healthy environment and supporting the achievement of the Sustainable Development Goals (SDGs), particularly the Open Defecation Free (ODF) target (Bappenas, 2023). Pangandaran Regency achieved 100% ODF status in 2023, but monitoring one year later revealed that Harumandala and Kertajaya Villages experienced setbacks, with some residents returning to open defecation practices. This study employs a qualitative approach with a case study method, involving ten competent informants. The findings indicate that although sanitarians have received STBM training, the implementation of triggering activities is hindered by a lack of human resources, limited funding from ADD and BOK, and inadequate understanding of STBM guidelines among informants. Additionally, transportation facilities are privately owned, and STBM planning is conducted annually, but no specific STBM organization has been established at Cigugur Health Center. Socialization efforts are carried out through triggering activities and counseling, with both direct and indirect supervision by relevant stakeholders. The main obstacle in maintaining ODF status is limited funding, which hinders the sustainability of the program. Therefore, a strong collective commitment and improved funding strategies are essential to ensure that Harumandala and Kertajaya Villages can regain and sustain their ODF status.